BIAYA PEMASANGAN BARU DAN PERHITUNGAN REKENING LISTRIK GOLONGAN TARIF RUMAH TANGGA - Baso Mukhlis (Foristek, 2012)
The problem of the society when it will require new electrical connection to PLN especially household bill level is the ignorance on the procedure and cost which have to be paid so that it asks helping to the brokers. This paper describes about how tocalculate cost of new connection installing which must be paid to PLN based on Kepmen ESDM No : 07 Tahun 2010, cost ofelectrical installation based on the amount of the power required, and how to calculate cost of usage based on new base rate 2010.